Action Research Report: Incremental Community Based Adaptation in the Highlands of Myanmar, Chin State - Barbon, Wilson John; Myae, Chan; Thant, Phyu Sin; Bernardo, Eisen Bernard; Gonsalves, Julian Francis (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
The International Institute of Rural Reconstruction (IIRR) undertook participatory action research in Myanmar to establish climate-smart villages (CSVs) in four unique agro-ecologies. This research was funded by CGIAR-CCAFS and the International Development Research Center in Canada (IDRC). Sakta Village is one of these four CSVs operated by IIRR and its local partner, Karuna Mission Social Solidarity (KMSS). It is located at Hakha Township in the north-east of Chin State situated 1,800 meters (6,000 feet) above sea level. After assessing local priorities and local knowledge, IIRR together with the community members identified and introduced 10 CSA options for Sakta Village. The number of participating households grew from 135 in 2018 to 158 in 2019 and 236 in 2020. Agroforestry-based diversification based on economically valuable trees helped farmers to incrementally adapt to a changing environment. Avocado, orange, and plums were found to be suitable with these high elevation sites. Home gardens emerged as an attractive CSA option, because it built on local knowledge. Mechanisms for local financing or natural- asset building were popular in homesteads.